MELODRAMA IN TIMES OF STREAMING - Lopes, Maria Immacolata Vassallo de (MELODRAMA IN TIMES OF STREAMINGS)
This Obitel yearbook brings“Melodrama in times of streaming” as the topic of the year. It aims to identify, through the analysis of the characters, themes and narrative plots of melodrama that are circulating on VoD platforms, the particularities of